Gen Z in work : a practical guide to engaging employees across the generations - Ochis, Karina (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This concise and clear book provides actionable solutions to every manager's and leader's newest problem: How to work effectively with Gen Z employees. Employee disengagement is a problem for businesses around the globe, with 85% of employees actively disengaged from their work. By 2025, Gen Z will account for one-third of the workforce, according to the World Economic Forum, and a growing challenge is how to adapt organisations to effectively include this group. Companies must now redesign long-established practices to include rapid integration, gamified rewards, mixed generation teams and multigeneration training in ways that will capitalize on the current behaviours of Gen Z, as well as other worker groups. This book provides: The measures companies can take to forge productive relationships between Gen Z and older, more experienced employees. An approach that can be readily applied by senior executives and managers to engage Gen Z employees and to address the disengagement problem more broadly. Implementable solutions on how five traditional practices - onboarding, leadership, culture, motivation and benefits - can be altered in companies to improve Gen Z productivity. The problem of disengagement is widespread across companies and industries, and results in diminished productivity, high turnover costs, and the loss of experienced professionals. Managers and leaders across all sectors will find this book indispensable in implementing an actionable strategy for improving the performance of Gen Z"--
Keywords: Generation Z -- Employment; Generation Z -- Attitudes; Conflict of generations in the workplace; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Careers / General